Update on fixation of rigid and foldable posterior chamber intraocular lenses, part II: choosing the correct haptic fixation and intraocular lens design to help eradicate posterior capsule opacification - Ram, Jagat; Apple, David J.; Peng, Qun; Visessook, Nithi; Auffarth, Gerd U.; Schoderbek, Robert J.; Ready, Edgar L. (Ophthalmology, 2003)
Posterior capsule opacification (PCO) is one of the most common complications of cataract surgery, and there is an urgent need to reduce its incidence…